UPAYA MENINGKATKAN HASIL BELAJAR IPAS DENGAN MENGGUNAKAN MEDIA GAMBAR PADA SISWA KELAS III SDN II TANJUNG INTEN - Indah Wulandari; Sulis Anjarwati; Nurkaif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve students’ learning outcomes in Natural and Social Sciences (IPAS) through the use of image media in third-grade students at SDN II Tanjung Inten. The research was motivated by low student learning outcomes, where most students did not achieve the minimum mastery criteria and showed low engagement during the learning process. This study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, acting, observing, and reflecting stages. The subjects of this study were 17 third-grade students. Data were collected through tests, observations, and documentation, and analyzed using descriptive quantitative and qualitative methods. The results showed a significant improvement in students’ learning outcomes. The average score increased from 60.6 in the pre-cycle to 72.6 in Cycle I, and further to 85.9 in Cycle II. The percentage of learning mastery also improved from 29.4% in the pre-cycle to 76.5% in Cycle I, and reached 94% in Cycle II, exceeding the success indicator of 80%. These findings indicate that the use of image media is effective in enhancing students’ understanding, engagement, and learning outcomes in IPAS. Therefore, image media can be considered an appropriate instructional strategy, especially for abstract learning materials in elementary education.